2019
DOI: 10.9734/sajrm/2019/v4i130096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Activity of Sida cordifolia Leaf Extract

Abstract: Objective: The objective of the study was to evaluate in-vitro efficacy of antibacterial, and antifungal activities of chloroform extract of leaf of Sida cordifolia L. against some human pathogenic bacterial and fungal strains. S. cordifolia (Malvaceae) is used as anti-rheumatic, analgesic, antipyretic, anti-asthmatic, nasal decongestant, antiviral, laxative, diuretic, aphrodisiac, hypoglycemic, hepatoprotective and in the treatment of Parkinson disease. Methodology: Chloroform extract of S.cordifolia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The ethanol extract of N. indicum leaves showed antifungal activity against Aspergillus niger and Candida albicans with zone of inhibition of 10 mm and 13 mm, respectively [15]. The phytochemical screening and in vitro efficacy of antimicrobial activities of chloroform leaf extract of Sida cordifolia L. were studied against some human pathogenic bacterial and fungal strains [16]. The extracts of some Cassia, Detarium, and Ziziphus species showed antifungal activity against dermatophytes [17].…”
Section: Discussionmentioning
confidence: 99%
“…The ethanol extract of N. indicum leaves showed antifungal activity against Aspergillus niger and Candida albicans with zone of inhibition of 10 mm and 13 mm, respectively [15]. The phytochemical screening and in vitro efficacy of antimicrobial activities of chloroform leaf extract of Sida cordifolia L. were studied against some human pathogenic bacterial and fungal strains [16]. The extracts of some Cassia, Detarium, and Ziziphus species showed antifungal activity against dermatophytes [17].…”
Section: Discussionmentioning
confidence: 99%
“…The authors have identified the presence of catechin, chlorogenic acid, rutin, and quercetin [29,30] compounds also identified in the extracts of G. hirsutum L., indicating a possible relation between the chemical content and biological activity of these species. Accordingly, a chloroformic extract obtained from Sida cordifolia (Malvaceae) showed antifungal activity against C. albicans, possibly due to the presence of flavonoids [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In its phytochemistry, there are compounds such as asparagine, tryptophan, alkaloids (ephedrine -sympathomimetics, hypaphoforine, vasicine, vasicinone, vasicinolbronchodilator), phytosterols, mucin, rutin and potassium nitrate [7,8] . Analgesic, anti-bacterial, antiinflammatory, hypoglycemic and hepatoprotective effects have also been reported in several studies [9,10] . In Brazil, it is used mainly as a natural anti-inflamatory [11] .…”
Section: Introductionmentioning
confidence: 92%